Propensity score-matched analysis of long-term outcomes for living kidney donation in alternative complement pathway diseases: A pilot study - VELİOĞLU, ARZU (My University, 2023)
Background Atypical hemolytic syndrome (aHUS) and C3 glomerulopathy (C3G) are complement-mediated rare diseases with excessive activation of the alternative pathway. Data to guide the evaluation of living-donor candidates for aHUS and C3G are very limited. The outcomes of living donors to recipients with aHUS and C3G (Complement disease-living donor group) were compared with a control group to improve our understanding of the clinical course and outcomes of living donation in this context.Methods Complement disease-living donor group [n = 28; aHUS(53.6%), C3G(46.4%)] and propensity score-matched control-living donor group (n = 28) were retrospectively identified from 4 centers (2003-2021) and followed for major cardiac events (MACE), de novo hypertension, thrombotic microangiopathy (TMA), cancer, death, estimated glomerular filtration rate (eGFR) and proteinuria after donation.Results None of the donors for recipients with complement-related kidney diseases experienced MACE or TMA whereas two donors in the control group developed MACE (7.1%) after 8 (IQR, 2.6-12.8) years (p = 0.15). New-onset hypertension was similar between complement disease and control donor groups (21.4% vs 25%, respectively, p = 0.75). There were no differences between study groups regarding last eGFR and proteinuria levels (p = 0.11 and p = 0.70, respectively). One related donor for a recipient with complement-related kidney disease developed gastric cancer and another related donor developed a brain tumor and died in the 4th year after donation (2, 7.1% vs none, p = 0.15). No recipient had donor-specific human leukocyte antigen antibodies at the time of transplantation. Median follow-up period of transplant recipients was 5 years (IQR, 3-7). Eleven (39.3%) recipients [aHUS (n = 3) and C3G (n = 8)] lost their allografts during the follow-up period. Causes of allograft loss were chronic antibody-mediated rejection in 6 recipients and recurrence of C3G in 5. Last serum creatinine and last eGFR of the remaining patients on follow up were 1.03 +/- 038 mg/dL and 73.2 +/- 19.9 m/min/1.73 m2 for aHUS patients and 1.30 +/- 0.23 mg/dL and 56.4 +/- 5.5 m/min/1.73 m2 for C3G patients.Conclusion The present study highlights the importance and complexity of living related-donor kidney transplant for patients with complement-related kidney disorders and motivates the need for further research to determine the optimal risk -assessment for living donor candidates to recipients with aHUS and C3G.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; ÜROLOJİ VE NEFROLOJİ; Klinik Tıp; Klinik Tıp (MED); UROLOGY & NEPHROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Üroloji; Urology; Atypical hemolytic uremic syndrome; Complement; C3 glomerulopathy; Kidney; Living donation; Transplantation; HEMOLYTIC-UREMIC SYNDROME; C3 GLOMERULOPATHY; TRANSPLANTATION; ACTIVATION; RECIPIENTS; Atypical hemolytic uremic syndrome; Complement; C3 glomerulopathy; Kidney; Living donation; Transplantation